Cost-benefit analysis of implementing minimum energy efficiency standards for household refrigerator-freezers in Malaysia - Mahlia, T.M.I.; Masjuki, Haji Hassan; Saidur, Rahman; Amalina, M.A. (Energy Policy, 2004)
The ownership of household electrical appliances especially refrigerator-freezer has increased rapidly in Malaysia. Almost every household in this country has a refrigerator-freezer. To reduce energy consumptiom in this sector the refrigerator is one of the top priorities of the energy efficiency program for household appliances. Malaysian authority is considering implementing minimum energy efficiency standards for refrigerator-freezer sometime in the coming year. This paper attempts to analyze cost-benefit of implementing minimum energy efficiency standards for household refrigerator-freezers in Malaysia. The calculations were made based on growth of ownership data for refrigerators in Malaysian households. The number of refrigerator-freezer has increased from 175,842 units in 1970 to 4,196,486 in 2000 and it will be about 11,293,043 in the year of 2020. Meanwhile it has accounted for about 26.3 of electricity consumption in a single household. Therefore, efficiency improvement of this appliance will give a significant impact in the future of electricity consumption in this country. Furthermore, it has been found that implementing an energy efficiency standard for household refrigerator-freezers is economically justified.